Minimum total distance clustering and balanced distance clustering in Northern Thailand's corn crop residue management system - Sirilak Phonin (2019)
© 2019 Author(s). The authors study the corn crop residue management system for 16 provinces in northern Thailand which encompasses 127 agricultural cooperatives (co-ops), 974 corn fields and 274 customers. To solve the system's problems, we find clusters where co-ops will pick up crop residues from corn fields, process them into it biomass fuel and sell the fuel to customers. Each cluster consists of a co-op, a set of corn fields and a set of customers, the latter two being on separate routes from the co-op. To minimize the system's transportation cost and balance transportation cost between clusters, we propose mathematical model and apply two modified heuristics.